'DIGITS' app - smartphone augmented reality for hand telerehabilitation. Issue 4 (4th July 2022) - Dong, Hongdao; Ho, Edward; Shin, Herbert; Banerjee, Tania; Masschelein, Geoffrey; Davidson, Jacob; de Ribaupierre, Sandrine; Eagleson, Roy; Symonette, Caitlin
ABSTRACT: Hand telerehabilitation currently has limitations for accurate and remote assessment of range of motion (ROM) in small finger joints. 'DIGITS' application utilises the front smartphone camera to measure finger ROM in a reliable and rapid assessment protocol. Our initial beta-phase testing examined the consistency of our software measurements to in-person goniometry. 6 to 9 degrees of difference existed between the smartphone application recorded data versus the in-person measurements. This range is within acceptable 7 to 9 degree tolerance for interrater goniometry measurements. The effect of environmental factors such as hand distance, lightings and hand orientation was evaluated. The intraclass correlation coefficient (ICC) was 0.98–0.98 for finger extension and 0.78–0.81 for finger flexion recorded across different environmental conditions. Overall, 'DIGITS' provides an augmented reality tool to generate reliable finger ROM tracking for hand telerehabilitation. 'DIGITS' has the potential to transform hand therapy and improve our knowledge of hand pathology recovery.